2012
DOI: 10.1143/apex.5.102104
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic Photoluminescence Properties of a Green-Emitting InGaN Single Quantum Well on a $\{20\bar{2}1\}$ GaN Substrate Probed by Scanning Near-Field Optical Microscopy

Abstract: Nanoscopic photoluminescence (PL) properties of a green-emitting {2021} InGaN single quantum well (SQW) are investigated by scanning near-field optical microscopy (SNOM). Carrier/exciton diffusion outside the probe aperture of 150 nm is demonstrated by a multimode SNOM technique. The estimated diffusion lengths are ∼70 nm along the [1014] direction and ∼50 nm along the [1210] direction, and are in between those of (1122) and (0001) InGaN QWs. This finding is well accounted for by the difference in carrier/exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…The large S-shaped shift behaviour of the peak energy is characteristic of the localization effect. The degree of the localization effect can be determined by fitting the temperature-dependent emission energy curve using the band-tail model636465: where E(T) is the emission energy at T, E g (0) is the energy gap at 0 K, and α and β are the Varshni coefficients. The third term originates from the localization effect, and σ indicates the degree of the localization effect, where in general, a larger value of σ corresponds to a stronger localization effect.…”
Section: Resultsmentioning
confidence: 99%
“…The large S-shaped shift behaviour of the peak energy is characteristic of the localization effect. The degree of the localization effect can be determined by fitting the temperature-dependent emission energy curve using the band-tail model636465: where E(T) is the emission energy at T, E g (0) is the energy gap at 0 K, and α and β are the Varshni coefficients. The third term originates from the localization effect, and σ indicates the degree of the localization effect, where in general, a larger value of σ corresponds to a stronger localization effect.…”
Section: Resultsmentioning
confidence: 99%
“…Such a systematic study on ð11 22Þ semipolar InGaN/GaN MQW with high indium content has not yet been reported, even on very expensive free-standing semipolar GaN substrates. [9][10][11][12][13][14]21 The ð11 22Þ semi-polar GaN has been obtained by overgrowth on nanorod templates, which were fabricated using our self-organized nickel nano-mask technique. 6,7 Four samples, each with five periods of InGaN/GaN MQWs were grown on the overgrown ð11 22Þ GaN.…”
mentioning
confidence: 99%
“…This has also been observed on InGaN/GaN MQWs grown on free-standing GaN substrates. [9][10][11][12][13] A standard two exponential component model is used to study excitonic dynamics, and thus TRPL traces [I(t)] can be described by [16][17][18] IðtÞ ¼ A 1 expðÀt=s 1 Þ þ A 2 expðÀt=s 2 Þ:…”
mentioning
confidence: 99%
“…[6][7][8] In other cases, lower potential sites were found to occur in the same regions as an enhanced nonradiative recombination. This effect was observed in green emitting polar InGaN QWs, 7,9 certain semipolar InGaN QWs, 10,11 and AlGaN layers 12 and QWs. 13 In this work, we probe spatial band gap inhomogeneities in semipolar ð20 21Þ QWs by measuring near-field (NF) photoluminescence (PL) spectra.…”
Section: Introductionmentioning
confidence: 77%
“…Scanning NF optical microscopy allows mapping optical properties with subwavelength resolution, which has proved to be a powerful tool to study spatial variations of light emission in ternary nitride structures and devices. [6][7][8][10][11][12][13][14][15] Particularly, for ð20 21Þ InGaN QWs, NF PL measurements were previously reported for just one QW sample with x $ 0.30. 11 Rather large PL intensity variations occurring on a 100 nm scale were observed and assigned to features of the surface morphology.…”
Section: Introductionmentioning
confidence: 98%